TROVA outputs for the extratropical transition of tropical cyclones in the North Atlantic basin ... - Pérez-Alarcón, Albenis; Coll-Hidalgo, Patricia; Fernández-Alvarez, José C.; Trigo, Ricardo M.; Nieto, Raquel; Gimeno, Luis (Zenodo, 2023)
Output data from the TRansport Of water Vapor (TROVA) tool for the research paper "Evaluating changes in the moisture sources for tropical cyclones precipitation in the North Atlantic that underwent extratropical transition". ...